A study on perinatal factors associated with low-birth-weight neonates in a tertiary care centre in central India - Barange, Shubham; Anand, Shweta (International Journal of Contemporary Pediatrics, 2023)
Background: Low birth weight is a major public health issue worldwide, with a variety of both short- and long-term implications. Estimated to account for 15% to 20% of all births worldwide, India constitutes about 30% of all live births, i.e., nearly 3 million LBW babies are born per year in India. The study focuses on the factors which contribute to the low birth weight in a newborn. Methods: The present study was conducted as a cross sectional case control study at department of pediatrics, LN medical College and Research Centre, Bhopal for duration of 1.5 years i.e. from 1st February 2021 to 31st August 2022. 420 participants were enrolled of which 210 were of cases (low birth weight group) and 210 were taken to the control group (normal birth weight group). After obtaining ethical clearance from institute’s ethical committee, all the participants fulfilling the inclusion criteria were enrolled. Chi square test was used to test the association between categorical variables. Results: Maternal age, weight, height, maternal diseases came out to be significant factors associated to the low birth weight of the neonate in this study. Conclusions: The study gains new insights into the perinatal factors associated with low-birth-weight newborn. Many risks for LBW can be identified even before pregnancy. As revealed by the study, well established socio-economic, obstetric, medical and behavioural health related determinants of LBW are seen quite prevalent in our tertiary care centre.